Increasing Self-Esteem of Schizophrenia Clients Through Online Clinical Practice - Wiwi Olivia; Ice Yulia Wardani; Yunita Astriani Hardayati (Jurnal Ilmu Keperawatan Jiwa, 2020)
Schizophrenia is defined as a collection of symptoms that can cause serious psychiatric problems, and one of the negative symptoms of Schizophrenia is low self-esteem. Low self-esteem is a negative self-evaluation of oneself which causes feelings of worthlessness, insignificance, low self-esteem, and if it is prolonged, it is called chronic low self-esteem (HDRK). HDRK is owned by a 30 year old man with a medical diagnosis of Schizophrenia. Clients experience HDRK because they feel they have cognitive deficits. The application of mental nursing care standards aims to make the client have a self-concept; optimal confidence. Nursing intervention that is carried out is to identify and train the abilities or positive aspects possessed by the client. The purpose of this case study is to analyze the results of mental nursing care provided to schizophrenia clients in increasing self-esteem during the online Covid-19 pandemic. The method used in writing is a case report which Ade carried laut for 20 days with a total 0f 14 meetings online via videocall whatsapp. The results of this scientific work show that clients experience an increase in self-esteem after being given mental nursing care online. The effectiveness of the application of standards of nursing care in increasing the self-esteem given to clients is shown by decreasing the signs of low self-esteem in cognitive, affective, behavioral, physiological, and social responses.